Production of Fish-Bioactive Peptides by Conventional & Emerging Technologies: A Review - Muhammad Alfid Kurnianto; Salma Shafrina Aulia (Nusantara Science and Technology Proceedings, 2023)
Fish is a type of food that is perishable. High production and perishable characteristics cause fish commodities to be immediately given storage or processing treatment so that they do not decrease in quality. The processing of fishery commodities has focused on producing foods with health effects for humans, such as functional foods, functional ingredients, and nutraceuticals. The health effects are caused by the content of bioactive compounds, one of which is bioactive peptides. Bioactive peptides are fragments from hydrolysis and have several biological functionalities such as antioxidant, anti-inflammatory, antihypertensive, anti-obesity, antimicrobial, and immunomodulatory properties. Generally, bioactive peptides can be produced from substrates such as foods with high protein content using enzymatic hydrolysis, chemical hydrolysis, and microbial fermentation technologies. However, these methods result in low peptide yields. Several emerging technologies have been applied in producing bioactive peptides, such as Ultrasound-Assisted Processing, Microwave-Assisted Processing, High Hydrostatic Pressure Processing, and Pulsed-Electric Field Processing. The application of emerging technologies is expected to produce peptides with high yield, fast, and low cost.